In 1911, Baoding epidemic prevention propaganda research (The Journal of Medicine, Humanity and Media, 2024)
At the end of the Qing Dynasty, the plague broke out in Northeast China, and Baoding was particularly valued by the Qing court for its epidemic prevention and control due to its special political status and transportation status. In January 1911, after the outbreak of the epidemic in Zhili, Baoding quickly established an epidemic prevention mechanism with the Epidemic Prevention Bureau as the core. Until April 13, 1911, the Baoding Provisional Epidemic Prevention Bureau was officially abolished, and the epidemic prevention work of nearly three months was declared to be over. Based on the 1911 Baoding plague prevention and control propaganda, this paper uses newspapers and periodicals as the main materials, and discusses the consideration of public opinion propaganda by local governments in major health events in the late Qing Dynasty, and how to achieve effective communication with the general public, so as to achieve the purpose of the smooth development of the epidemic prevention policy.
Keywords: Baoding; plague; epidemic prevention propaganda; vernacular